Acute ibuprofen ingestion does not attenuate fatigue during maximal intermittent knee extensor or all-out cycling exercise - Morgan, P. T.; Vanhatalo, A.; Bowtell, J. L.; Jones, A. M.; Bailey, S. J. (Applied Physiology, Nutrition, and Metabolism, 2019)
Recent research suggests that acute consumption of pharmacological analgesics can improve exercise performance, but the ergogenic potential of ibuprofen (IBP) administration is poorly understood. This study tested the hypothesis that IBP administration would enhance maximal exercise performance. In one study, 13 physically active males completed 60 × 3-s maximal voluntary contractions (MVCs) of the knee extensors interspersed with 2-s passive recovery periods, on 2 occasions, with the critical torque (CT) estimated as the mean torque over the last 12 contractions (part A). In another study, 16 active males completed two 3-min all-out tests against a fixed resistance on an electronically braked cycle ergometer, with the critical power estimated from the mean power output over the final 30 s of the test (part B). All tests were completed 60 min after ingestion of maltodextrin (placebo, PL) or 400 mg of IBP. Peripheral nerve stimulation was administered at regular intervals and electromyography was measured throughout. For part A, mean torque (IBP: 60% ± 13% of pre-exercise MVC; PL: 58% ± 14% of pre-exercise MVC) and CT (IBP: 41% ± 16% of pre-exercise MVC; PL: 40% ± 15% of pre-exercise MVC) were not different between conditions (P > 0.05). For part B, end-test power output (IBP: 292 ± 28 W; PL: 288 ± 31 W) and work done (IBP: 65.9 ± 5.9 kJ; PL: 65.4 ± 6.4 kJ) during the 3-min all-out cycling tests were not different between conditions (all P > 0.05). For both studies, neuromuscular fatigue declined at a similar rate in both conditions (P > 0.05). In conclusion, acute ingestion of 400 mg of IBP does not improve single-leg or maximal cycling performance in healthy humans.